Left Heart Dysfunction in Acromegaly Revealed by Novel Echocardiographic Methods - Uziȩbło-Życzkowska, Beata; Jurek, Agnieszka; Witek, Przemysław; Zieliński, Grzegorz; Gielerak, Grzegorz; Krzesiński, Paweł (Frontiers in Endocrinology, 2020)
Background: Acromegaly is a rare disease that requires modern treatment to decrease the risk of mortality, mainly from vascular diseases. Identifying acromegalic patients with increased cardiovascular risk is challenging. Speckle-tracking echocardiography (STE) is a modern, well-validated, and reproducible method of assessing left ventricular longitudinal deformation and providing a sensitive assessment of myocardial contractility. We hypothesized that STE may be useful in evaluating subclinical dysfunction of the left heart in acromegalic patients, especially when a left ventricle (LV) assessment is completed with STE of the left atrium (LA). Purpose: To assess the diagnostic value of speckle-tracking echocardiography in identifying the occurrence of LV and LA functional impairment in patients with acromegaly, in comparison to patients without this rare pituitary disease. Methods: Echocardiographic assessments of LV and LA function using the new STE method were performed in 60 subjects: 30 acromegalic (ACRO group) patients and a CONTROL group with 30 patients matched in terms of age, gender, systolic/diastolic pressure, and history of hypertension for least 12 months. Results: The ACRO group, compared to the CONTROL group, presented: 1) higher left ventricular mass (left ventricular mass index: 132g/m2 vs. 108 g/ m2, p < 0.001) and, in consequence, more frequent LV hypertrophy (80.0% vs. 53.3%; p = 0.028); 2) impaired LV systolic function measured by both left ventricular ejection fraction (LVEF) (63.4% vs. 66.9%, p < 0.001) and global longitudinal strain (GLS) (-18.1% vs -19.4%, p = 0.023); 3) greater LA anteroposterior diameter (40.3 mm vs. 36.9 mm, p = 0.003) and indexed left atrial volume (37.9 ml/m2 vs. 27.6 ml/m2, p < 0.001); and 4) impaired echocardiographic strain parameters corresponding with LA function. Conclusions: Acromegaly, even in young patients with good blood pressure control, may be associated with left ventricular hypertrophy and subclinical impairment of the left ventricular and left atrial mechanical function, which may be identified by speckle-tracking echocardiography. Further research in this area is necessary to clarify the prognostic value of these phenomena.